GLOBAL DEBATE: ON NUCLEAR LAW - Korolev, Yuriy (Актуальні проблеми правознавства, 2024)
The International Atomic Energy Agency (IAEA) plays a unique role in the development and implementation of international nuclear law. This chapter contains a short examination of the regime of nuclear law and its four pillars, namely safety, security, safeguards and civil liability for nuclear damage. The development and utilization of nuclear energy is one of the greatest achievements of the 20th century. It has greatly enhanced the ability of humanity to understand and shape the world and had a significant impact on the development of technology and civilization. To this end, nuclear energy offers unique advantages, but the associated risks and challenges of its further development and utilization must be addressed. Nuclear law is a powerful tool for regulating its development and responding to those risks and challenges.